49 - CHARACTERIZATION OF INJURIES AND PAINFUL PROCESS IN BURNS VICTMS: A STUDY OF PATIENTS ADIMITTED TO AN EMERGENCY HOSPITAL, NATAL/RN. (Fiep Bulletin - online, 2011)
Introdution: burn injuries are among the worst damages people can suffer. It can be conceptualized as the product resulting from direct and indirect action of heat on the human organism, and can be caused by domestic accidents, aggression and suicide. Objectives: to identify the burned patients who seek assistance at Monsignor Walfredo Gurgel Hospital / Emergency Clóvis Sarinho; identify the severity of injuries and the painful impact level in these patients; identify if there is significant difference between pain reported by the patient in the first and second week after the burn. Method: it´s an exploratory-descriptive and quantitative study with prospective data, carried out in the Hospital Monsenhor Walfredo Gurgel (HMWG), in Natal / RN. The target population consisted of 30 patient victims of burn injuries, who were hospitalized for treatment in HMWG during the data collection of this research. Results: it was detected a young population aged between 20 and 30 years (53.3%), equal proportions between genders, and 23 (76.7%) were from Natal. Regarding to burn injuries data, the most common was caused by domestic (40.0%), with prevalence of burns of middle extension (80%) and 2-degree depth (83.3%) and the most affected were the upper limbs, with 70% of cases. Concerning to the pain complaint, as in the first week 50% attributed a score of 10 to pain in the second week, only 13.3% of them gave the maximum score. Conclusion: Burns and its complications were the main causes of death worldwide, causing very intense painful sensations, but even knowing the importance and severity of pain, it is still undervalued in the therapeutic process. It leads to direct and indirect losses for the assistance, and for the recovery of the patient.
Keywords: Burn; Pain Measurement; Nursing